The Witching of Art History - or How to Approach Women, Art and Esotericism - Kokkinen, Nina (Approaching religion, 2025)
The special issue "The Witching of Art History" examines how women and artists beyond gender binaries have navigated artistic and occult subjectivities, identities and agency within art and occulture since the 19th century. The articles illuminate the mechanisms, structures and discursive distinctions that have shaped the experiences of artist women, as well as the strategies they have employed to negotiate these challenges. The issue introduces new conceptual frameworks for the study of art and esotericism - such as feminist ecoaesthetics, magical futurist art and seeker as weaver - alongside perspectives that challenge male-centred narratives. Here, "witching" functions as a political term, inviting a reimagining of normative approaches to art history and its intersections with esotericism, occultism and magic. The title draws inspiration from contemporary art practice, reflecting how artists have reclaimed the figure of "the witch" - once stigmatised as evil and perverse - and transformed it into a symbol of empowerment. In doing so, the issue foregrounds the significant contributions of artist women not only within the art world but also across diverse spheres of occulture, where modern religiosity has been reshaped. All articles were peer-reviewed and further developed through discussions at the international seminar "The Witching of Art History", held at the Ateneum Art Museum and the University of Helsinki on 20-21 August 2025. The seminar and this thematic issue share a common aim: to emphasise the central role of women in art and esotericism while engaging critically with theoretical and methodological questions.